2013
DOI: 10.1016/j.cub.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Stomatal Response to Reduced Relative Humidity Requires Guard Cell-Autonomous ABA Synthesis

Abstract: Stomata are pores on the leaf surface, bounded by two guard cells, which control the uptake of CO(2) for photosynthesis and the concomitant loss of water vapor. In 1898, Francis Darwin showed that stomata close in response to reduced atmospheric relative humidity (rh); however, our understanding of the signaling pathway responsible for coupling changes in rh to alterations in stomatal aperture is fragmentary. The results presented here highlight the primacy of abscisic acid (ABA) in the stomatal response to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
369
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(403 citation statements)
references
References 28 publications
15
369
2
1
Order By: Relevance
“…1C). This could be explained by increased ABA levels induced by low air humidity, as observed in other species (Bauer et al, 2013;McAdam and Brodribb, 2015), which could potentially lead to partial ABA-induced closure of the stomata of ferns grown in the growth room and no further effect of ABA treatment on stomatal conductance. If the ABA response is already activated in ferns grown at lower RH, these plants would be expected to have lower stomatal conductance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). This could be explained by increased ABA levels induced by low air humidity, as observed in other species (Bauer et al, 2013;McAdam and Brodribb, 2015), which could potentially lead to partial ABA-induced closure of the stomata of ferns grown in the growth room and no further effect of ABA treatment on stomatal conductance. If the ABA response is already activated in ferns grown at lower RH, these plants would be expected to have lower stomatal conductance.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest a greater flexibility and faster stomatal responsiveness to changes in vapor pressure deficit (VPD) in angiosperms. This could be expected, as the responses to changes in VPD are linked with the biosynthesis and presence of ABA (Bauer et al, 2013;McAdam and Brodribb, 2015) as well as ABA signaling (Merilo et al, 2013), and stomatal ABA responses in angiosperms are faster and stronger than in ferns (Brodribb and McAdam, 2011; Fig. 1, B and C).…”
Section: Stomatal Responses To Subambient and Above-ambient Co 2 Concmentioning
confidence: 96%
See 1 more Smart Citation
“…Until recently, little was known about the time dynamics for ABA biosynthesis, even though early studies suggested the water potential trigger for ABA synthesis occurred when leaf turgor approached zero Raschke, 1980, 1981). The role of guard cell biosynthesis of ABA in responses to humidity is also unclear (Bauer et al, 2013). However, by providing a way to predict the effect of constant leaf [ABA] on stomatal conductance on the backbone of a hydraulic model, the model here provides an important stepping stone for working toward a dynamic model including both water relations and ABA dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…11 It is well known that osmotic stress-derived ABA can reduce leaf hydraulic conductivity and shoot growth, thus reducing the transpiration rate in Arabidopsis leaves, [12][13][14] whereas it can maintain root water uptake by enhancing root growth and root hydraulic conductivity. 8,11,[15][16][17] Recently it is found that the single PYL8 ABA receptor play a key role in mediating ABA-controlled root growth and root response to moisture gradient, means hydrotropism, [17][18] while there is a obvious redundant characteristics of PYR1/PYL/RCAR ABA receptor family in stomatal aperture regulation.…”
mentioning
confidence: 99%